Investigating the implementation of information and communication technology-based English language teaching in Chinese independent high schools in west Malaysia - Mak, Vee Vien (2023)
The use of ICT has been one of the most discussed topics in education for the past twenty years. Notably, it has posited education in Chinese Independent High Schools (CIHS) in Malaysia to a more challenging platform due to several factors: their distinctions around the self-funding, medium of instruction and syllabus. Past studies found that although most teachers had positive attitudes toward ICT integration, some barriers might prevent them from fully utilising ICT in schools. In this study, the targeted respondents were those English teachers from CIHS in West Malaysia. It aimed to investigate teachers' perceptions and challenges while using ICT-based online learning in the teaching and learning process and some solutions from the teachers to overcome the obstacles. A mixed-method explanatory sequential research design was used in this study, in which the quantitative method was conducted first, followed by the qualitative approach to help explain and receive more data to supplement the quantitative results. 180 English teachers answered the questionnaire adapted from Qasem & Viswanathappa (2016) and Salehi & Salehi (2012). Among 180 respondents, 24 of them were selected for the interview sessions. The pilot study was done before the actual questionnaires v were distributed. Besides descriptive analysis, Reliability Test, T-Test and One-Way ANOVA were used to analyse the data collected via SPSS version 24. About two-thirds of the respondents in this study had an awareness towards the use of technology in education and perceived ICT in the teaching and learning process positively. The significant challenges faced by the English teachers in this study while using ICT to teach their students included insufficient time, teachers' attitude and interest, lack of skills and competence in ICT, teachers' teaching experiences, insufficient Internet coverage, lack of technical support from schools, lack of professional training on ICT, lack of accessibility and privacy on ICT, schools' views on ICT, lack of infrastructures and facilities provided on ICT by the school management, and students' attitudes on ICT. Constant training on using ICT in teaching should be provided to ensure a more successful implementation of ICT in education. Apart from this, adequate ICT resources must be made available for teachers. This study would be significant to educators, researchers, and school management to develop useful guidelines to assist teachers in overcoming the challenges of using ICT